Systemic Selection Of Training Methods And Technologies At The Academy Of The Arms Of The Republic Of Uzbekistan (Genius Repository, 2023)
Given article based on an experience of foreign higher military educational institutions, opens necessity of ordering of approaches to choose of various methods and technologies of training, according to the problems which are instructor (lecturer) put by itself before each exercise (lessons)